Genetic and environmental influences on the fibrinolytic system: a twin study - Peetz, Dirk; Victor, Anja; Adams, Petra; Erbes, Hilde; Hafner, Gerd; Lackner, Karl J.; Hoehler, Thomas (Thrombosis and Haemostasis, 2004)
The determination of heritability is a key issue to assess the predictive power of polymorphisms for disease in clinical studies. The aim of this study was to determine the heritability of proteins and activation markers of the fibrinolytic system in a large cohort of healthy twins. Heritability was calculated as 0.76 for thrombin activatable fibrinolysis inhibitor (TAFI), 0.44 for plasminogen activator inhibitor-1 (PAI-1), and 0.43 for tissue plasminogen activator. No significant genetic influence was observed for α2-antiplasmin-plasmin-complex and D-dimer. Heritability explained by single gene polymorphisms was 25.2% for TAFI 505G>A, 31.5% for 1542C>G, and 50.0% for combination of both. The influence on TAFI levels of 1542C>G (CC→GG, median: −280.5%) was considerably stronger than that of 505G>A (GG→AA, median: +49.3%) and in both cases there seems to be a dose-response relationship. Significant environmental influences on TAFI levels were observed for combined interaction terms (age*sex and bmi*sex). The PAI-1 4G/5G polymorphism explained 56.4% of the calculated heritability. The genetic variables accounting for the 43% heritability of tPA remain unknown. Our data show that the production of several key components of the fibrinolytic system is strongly genetically determined. This genetic influence is accounted for in large part but not completely by a limited number of polymorphisms within the respective genes associated with plasma levels of the gene products.
Keywords: Fibrinolysis inhibitors; thrombin activatable fibrinolysis inhibitor (TAFI) / carboxypeptidases; gene mutations; plasminogen activators